Mucormycosis of the Palate - Thimmarasa, VB; Devi, P; Mehrotra, V; Gupta, M (Journal of Armed Forces Medical College, Bangladesh, 2010)
Mucormycosis is an invasive, potentially lethal fulminant fungal infection that is caused by normally saprophytic fungus belonging to the class zygomycetes. Mucormycosis is characterized by its unrelenting progression towards vital organs with marked propensity towards arterial wall by direct extension producing vascular thrombosis leading to ischaemic necrosis. The maxilla rarely undergoes necrosis due to its rich vascularity. The case report here was a case of mucormycosis with extensive necrosis of maxilla in a 48 year old male patient with palatal perforation as the sole presentation of mucormycosis. Key words: Mucormycosis; palatal perforation; fungal infection. DOI: 10.3329/jafmc.v6i1.5989 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.29-31